Distal Ulna Leiomyosarcoma Treated with Custom Polymethylmethacrylate Prosthesis with a 4-Year Follow-up. (September 2015) - Pacheco-Nuñez, Jose Arturo; Sheppard, Joseph E.; Mahoney, Andrew P.
Background: Intraosseous leiomyosarcoma is a rare neoplasm having an aggressive biologic behavior. The distal end of the ulna is a very uncommon site for this type of primary bone tumor frequently mistaken for benign lesions. En bloc resection of the distal ulna with reconstruction is a valid option as a limb salvage procedure for the treatment of this difficult problem, minimizing local recurrence while preserving hand function. Case description: We present an unusual case of a 63-year-old woman with a primary leiomyosarcoma arising from the distal end of the ulna treated successfully with a wide excision and custom distal ulna, with 4-year follow-up and no recurrence. Literature review: Tumors to develop at the distal end of the ulna have been reported as part of large series such as Dahlin and few case reports. According to Cooney, Exner, and Mankin, reconstruction for distal ulnar neoplasms is not necessary to maintain function. However, Noble and Laurentin-Perez disagree because stabilization of the distal ulna following large resection, as in our case, can be a significant problem with associated pain and weakness due to a decreased interosseous space with ulnar stump impingement on the radial metaphysis and ulnar translation of the carpus. Clinical relevance Custom methacrylate in situ radioulnar joint prosthesis for reconstruction of a large segment of the distal ulna can be a valid option to reestablish the mechanical continuity of the forearm, reducing pain and improving strength and function.